2011
DOI: 10.1007/s00127-011-0372-x
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and psychotropic medication: a prospective cohort study

Abstract: Adjustment of work environments by reducing mental strenuousness and improving job satisfaction might help in prevention of mental health problems that account for a major part of the disease burden among employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
2
18
1
5
Order By: Relevance
“…We excluded metaanalyses (but extracted relevant studies from those) (18,19,25,26), reviews (5, 8-17, 21, 23), and books (20,22,24). We also excluded studies with overlapping data with selected studies (33)(34)(35)(36)(37)(38)(39)(40), those without adjustment for baseline mental health (41)(42)(43), and those prospective studies in which exposure and outcome were temporally overlapping (44,45). However, we performed a descriptive, qualitative analysis of studies which included prospective analysis with continuous outcomes rather than outcomes indicating onset of illness (46,47), a study with exposure treated as a continuous variable (48), longitudinal within-subject design with continuous outcomes (49), and broader mental health outcomes, such as antidepressant use (50, 51), all treated mental disorders (52), or disability claims due to all mental disorders (53).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…We excluded metaanalyses (but extracted relevant studies from those) (18,19,25,26), reviews (5, 8-17, 21, 23), and books (20,22,24). We also excluded studies with overlapping data with selected studies (33)(34)(35)(36)(37)(38)(39)(40), those without adjustment for baseline mental health (41)(42)(43), and those prospective studies in which exposure and outcome were temporally overlapping (44,45). However, we performed a descriptive, qualitative analysis of studies which included prospective analysis with continuous outcomes rather than outcomes indicating onset of illness (46,47), a study with exposure treated as a continuous variable (48), longitudinal within-subject design with continuous outcomes (49), and broader mental health outcomes, such as antidepressant use (50, 51), all treated mental disorders (52), or disability claims due to all mental disorders (53).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…We believe, however, that any such bias was mitigated by our deci- Hannerz et al formed in a population-based Canadian study, which treated working hours as a continuous variable and estimated that the incidence of psychotropic drug usage decreased with weekly working hours RR=0.99 (95% CI 0.98-1.00) (37). The other was performed in a Finnish study, which estimated the RR for psychotropic drug usage among female employees of the City of Helsinki to be 0.96 (95% CI 0.77-1.18) for the contrast >40 versus ≤40 working hours/week (38).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…Bonde and colleagues (Bonde et al, 2009) found no relationship between poor psychosocial work environment among 21,129 Danish public service employees and prescription of antidepressant pharmaceuticals (Bonde et al, 2009). After exclusion of current and regular users of psychotropic drugs, Laaksonen and colleagues (Laaksonen et al, 2012) found that working conditions were only weakly associated with psychotropic 8 medication. The workplace environment was of importance only among men.…”
Section: Simultaneous Equationsmentioning
confidence: 99%
“…Generally researchers have found that the impact of employment on the use of prescribed medication for mental wellbeing is rather weak (Bonde et al, 2009;Laaksonen et al, 2012;Virtanen et al, 2007). Investigating work stress, Virtanen and colleagues (Virtanen et al, 2007) showed that the association with future antidepressant use was evident only among male workers and not female workers (Virtanen et al, 2007).…”
Section: Simultaneous Equationsmentioning
confidence: 99%
See 1 more Smart Citation